Literature, American style : the originality of imitation in the early Republic - Tawil, Ezra F., 1967- (University of Pennsylvania Press, 2018)
Literature, American Style finds early U.S. authors self-consciously imitating European literary forms even as they claimed radical originality. The notion of style helped them manage this peculiar contradiction. It was their American use of style, they claimed, that marked their departure from literary precedents.